Subiektywne poczucie satysfakcji życiowej osób starszych - Gregorczuk-Prosicka, Joanna (Kultura-Społeczeństwo-Edukacja, 2021)
Life satisfaction is a complex and highly subjective concept. Scholars studying this issue have made numerous attempts to define it. Whether we are happy, or have a sense of fulfilment, or we delight in the years we have lived through and in everyday life, it is all related to the aforementioned life satisfaction. The article deals with the subjective sense of life satisfaction among elderly people who are members of the Senior Club in a rural-urban district. The article is based on material obtained from in-depth interviewing. The research objective was to explore and obtain thorough knowledge of the sense of life satisfaction of elderly people. Particular attention is paid to selected factors that determined the perception of life satisfaction. On the basis of the participants’ opinions, certain groups of factors were selected that were more often indicated as key factors in the assessment of life satisfaction, i.e. health, housing situation, place of residence, family relations, neighbourly relations and a sense of social utility. The article presents the complexity of the problem and the need for an individual approach to the topic, due to the changing face of ageing and old age.